1998
DOI: 10.1182/blood.v91.7.2547
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Signal Transduction Pathways in Human Eosinophils Activated by Chemoattractants and the T-Helper 2–Derived Cytokines Interleukin-4 and Interleukin-5

Abstract: Activation and recruitment of eosinophils in allergic inflammation is in part mediated by chemoattractants and T-helper 2 (Th2)-derived cytokines. However, little is known concerning the signal transduction mechanisms by which this activation occurs. We have investigated tyrosine kinase-mediated activation of phosphatidylinositol 3-kinase (PI3K) and compared this with the activation of the p21ras-ERK signaling pathway in human eosinophils. The related cytokines interleukin-3 (IL-3), IL-5, and granulocyte-macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0
2

Year Published

1998
1998
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(47 citation statements)
references
References 66 publications
5
39
0
2
Order By: Relevance
“…In normal eosinophils, PAF has previously been shown to induce the transient phosphorylation of several proteins [25]. Our attempts to identify differential expression of tyrosine phosphorylation in HES and normal eosinophils 1 h after PAF stimulation, however, were not revealing.…”
Section: Discussionmentioning
confidence: 71%
“…In normal eosinophils, PAF has previously been shown to induce the transient phosphorylation of several proteins [25]. Our attempts to identify differential expression of tyrosine phosphorylation in HES and normal eosinophils 1 h after PAF stimulation, however, were not revealing.…”
Section: Discussionmentioning
confidence: 71%
“…After incubation for 30 min cells were harvested in 23 SDS sample buffer, and lysates were subjected to Western blotting with antibodies to phospho-Akt and total Akt (A and C), as well as phospho-PDGFR and total PDGFR (B and D). potential mechanism for growth factor receptor-independent activation of PI3-K involves cyclic adenosine 39:59monophosphate (cAMP) -mediated signaling because agents that raise intracellular cAMP levels can activate both PI3-K and Akt (31,48). In addition, it has been reported that Akt is activated by G-protein-coupled receptors (GPCR) and that the pathway connecting G-proteins to Akt implicates signals emanating from Ga q , Ga i , and G bc dimers through a pathway that involves PI3-K activity (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Akt is generally activated through a PI3-K-mediated mechanism, although it is also activated independent of PI3-K under some circumstances (31). Other oxidants, H 2 O 2 and ONOO ÿ , induce Akt activation by a PI3-K-dependent mechanism (14,19).…”
Section: Induction Of Akt Phosphorylation By 1 O 2 Is Dependent On Pi3-kmentioning
confidence: 99%
“…Several lines of evidence have suggested that chemokine receptor signaling activates Akt prior to occurrence of PI3Kg gene deletion. These involve IL-8, SDF-1, MIP-1a and RANTES (333)(334)(335). However, the biological meaning of the chemokine receptor-mediated Akt activation remains unknown.…”
Section: Activation Of Akt By Chemokine: Chemotaxis or Cell Survivalmentioning
confidence: 99%